2021
DOI: 10.29271/jcpsp.2021.01.21
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Red Distribution Width (RDW) Value in Gastric Cancer

Abstract: Objective: To investigate the prognostic effect of red distribution width (RDW) in patients with gastric cancer. Study Design: Observational study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…RDW is a widely used laboratory parameter to measure the degree of erythrocyte anisocytosis, which reflects the variability in the size of circulating erythrocytes. 7 There was a signifi-cant difference in RDW values between CG -EG (p = 0.012), CG -MG (p = 0.003). This indicated that patients with acute DVT had an increased RDW value when they first came to the hospital.…”
Section: Discussionmentioning
confidence: 90%
“…RDW is a widely used laboratory parameter to measure the degree of erythrocyte anisocytosis, which reflects the variability in the size of circulating erythrocytes. 7 There was a signifi-cant difference in RDW values between CG -EG (p = 0.012), CG -MG (p = 0.003). This indicated that patients with acute DVT had an increased RDW value when they first came to the hospital.…”
Section: Discussionmentioning
confidence: 90%
“…Although the exact reason for the signi cant association of RDW with diagnosis and prognosis is not fully understood, it has been suggested that it may be related to erythropoietin inhibition and the shortened lifespan of red blood cells due to oxidative stress, which are important markers of in ammation (12). Furthermore, there are various research associated to RDW in terms of cancer diagnosis and prognosis (12,(14)(15)(16). However, in this study, an RDW value above 16.1 was found to positively predict the malignant potential of pancreatic cysts with a sensitivity of 93.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact reason for the signi cant association of RDW with diagnosis and prognosis is not fully understood, it has been suggested that it may be related to erythropoietin inhibition and the shortened lifespan of red blood cells due to oxidative stress, which are important markers of in ammation (12). Furthermore, there are various research associated to RDW in terms of cancer diagnosis and prognosis (12,(14)(15)(16). However, in this study, an RDW value above 16.1 was found to positively predict the malignant potential of pancreatic cysts with a sensitivity of 93.8%, making it the rst study to suggest that RDW can be used in the differentiation of benign and malignant cysts, providing a speci c cut-off value.…”
Section: Discussionmentioning
confidence: 99%